KEHIDUPAN TOKOH NARUTO SEBAGAI NINJA DALAM MANGA NARUTO KARYA MASASHI KISHIMOTO - Julyana Dewi, Jadek (Humanis, 2015)
The study title is “The Life of Naruto as a Ninja in Naruto Manga by Masashi Kishimoto”. This study focuses on the lives of Naruto as a ninja and comparison between Naruto life as a ninja with the social fact about ninja in Japanese society. The theory used to analyze the life and character in the manga Naruto ninja’s life and a fact of Japanese society is sociological literary theory from Damono (1979), and are using the semiotic theories of Luxembung (1992) to analyze image. The results of this study indicate that the figures in an effort to become a ninja Naruto is a gradual training, such as 1) Following training gakuin level; 2) Following genin level training; 3) Following the chuunin exams; 4) Attempting to enhance rasengan moves; and 5) Trying to protect the village of Konohagakure. There are also similarities and difference in the facts of ninja life in Naruto manga, such as1) Equation in ninja moves; 2) Equation in the governance structure of the ninja; 3) Equation in ninja weaponary; and 4) In equation ninja magic. While the difference such as 1) Difference in ninja training system; 2) Difference in the regulation of ninja training; 3) Difference in the use of ninja skills; and 4) The difference in the costume of the ninja.
Keywords: Ninja, manga, sociology of literature